Irregular Immigration : an Economic Analysis of Policies in the EU. - Minter, Steffen (Beiträge zur Finanzwissenschaft., 2015)
Irregular immigration is at the forefront of the political and public debate in the European Union. Images of desperate people arriving at the southern shores of the EU regularly dominate the media coverage. In this book, Steffen Minter focuses on the coordination problems between EU Member States in dealing with immigrants and refugees entering the EU. The author demonstrates that the enforcement of the external EU border constitutes a public good as long as irregular immigrants have the possibility to move on between member states once they have entered EU territory. In this scenario he anal.